2018
DOI: 10.1111/jan.13568
|View full text |Cite
|
Sign up to set email alerts
|

The impact of menopause on the sexual health of Chinese Cantonese women: A mixed methods study

Abstract: This study gives further knowledge for healthcare providers and policy makers to develop appropriate strategies and deliver suitable services to improve the quality of sexual health of menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
(72 reference statements)
3
15
1
2
Order By: Relevance
“…Men form a critical source of support in helping their women to cope with some of the challenges associated with menopause (Reale Caçapava Rodolpho et al, 2016). They are also crucial in reducing the influence of menopause on the sexual health of older women (Wong, Huang, Cheung, & Wong, 2018). Nonetheless, the gerontological literature is lacking in studies focusing on older men's perceptions of menopause and the possible influence on the values on sexuality in old age.…”
Section: Introductionmentioning
confidence: 99%
“…Men form a critical source of support in helping their women to cope with some of the challenges associated with menopause (Reale Caçapava Rodolpho et al, 2016). They are also crucial in reducing the influence of menopause on the sexual health of older women (Wong, Huang, Cheung, & Wong, 2018). Nonetheless, the gerontological literature is lacking in studies focusing on older men's perceptions of menopause and the possible influence on the values on sexuality in old age.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoactive sexual desire is the most commonly found symptom among female sexual dysfunctions. 20,32,34 Research data with Colombian women who reported sexual activity in the 4 weeks prior to being asked showed that, also in the postmenopause, sexual desire was the most deteriorated domain. 35 A data observed in the present study was that the prevalence of sexual dysfunction in women from Teresina, detected by the application of the SQ-F (64.0%), was similar to the report of sexual problems on the MRS scale (64.7%), emphasizing that most of the women surveyed had already identified some dissatisfaction in their sex life.…”
mentioning
confidence: 99%
“…During menopause, sexual incompatibility occurs between couples [ 22 ]. Women who experience menopause are more vulnerable to marital problems [ 23 ]. Satisfaction with the husband and children affects the menopausal symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%